Sistem Pakar Diagnosa Kerusakan Dan Perkiraan Biaya Servis Handphone Pada Toko Felix’z Mobile Tanjungpinang - Manihuruk, Wan Hendra; Darmawan Mega Permana; Dian Novryanto (LPPM Sekolah Tinggi Teknologi Indonesia Tanjung Pinang, 2018)
Toko Felix'z Mobile is a shop that provides cellphone services and sells various kinds of cellphone accessories, located on Jalan Bridjen Kata mso km 2 Tanjungpinang, Riau Islands. In this research the author will build an expert system at the Felix'z Mobile Store. A check is carried out manually in the sense that it is still using an electronic device to check the damage that has occurred to the cellphone. Due to this it takes a long time so the cellphone service is quite long. The software used as a tool for research and design of new systems is using Java Netbeans 8.1, and the database is MySQL Front. The results of the development of the system are expected to provide fast, accurate and efficient work potential so as to increase the potential of the shop.